Marketing of the Nanyang Business report series to the local and global markets. - Chang, Tze Ai. (2008)
Using segmenting, targeting and positioning concepts to develop a marketing strategy for the NBRS. The proposed strategy seeks to solve the fundamental backlog problem. In addition, Internet issues such as epublishing and eretailing are examined. Lastly, feasibility of epublishing for future publication is evaluated.